AN INQUIRY INTO THE CAUSES OF ILLEGAL OCCUPATION OF LAND IN ZAMBIA’S CITIES: A Case of Kitwe City - Anthony Mushinge; Alex Mumbaala Simposya; Ngosa Mukeya (African Journal on Land Policy and Geospatial Sciences, 2022)
Like in a number of other developing countries, the issue of illegal occupation of land is evident in Zambia’s cities. This problem has continued to exist, despite the existence of laws and public institutions meant to address the issue. The objectives of this paper were to establish the factors that lead to continued illegal land occupation in Zambia’s cities, establish the consequences of illegal occupation of land, and suggest how illegal occupation of land can be eradicated. Using evidence from the city of Kitwe, the study used both secondary and primary data to conclude that illegal land occupation in Zambian cities has continued to occur due to various factors. These factors include cumbersome land acquisition procedure, high land fees, weak enforcement of development control laws, inadequate monitoring of land use, land speculation, illegal allocation of land by some city council officials and councillors, under development of rural areas, and rapid increase in urban population. Illegal occupation of land has consequences which included demolition of property, disruption in land use planning, and loss of city councils’ revenue. In view of the foregoing, illegal occupation of land can be addressed through a number of means, which include: streamlining land acquisition procedure; reducing land fees for public land; ensuring effective enforcement of development control laws; ensuring adequate monitoring of land use; eradicating illegal allocation of land by some councillors and council employees; and improving living conditions in rural areas.